Does vitamin D supplementation benefit, harm, or have no effects on pregnant women or their babies? - article Editorial (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2024)
This article is the Russian translation of the Plain Language Summary (PLS) of the Cochrane Review previously published in the Cochrane Database of Systematic Reviews. Original publication: Palacios C, Kostiuk LL, Cuthbert A, Weeks J. Vitamin D supplementation for women during pregnancy. Cochrane Database Syst Rev. 2024;7(7):CD008873. https://doi.org/10.1002/14651858.CD008873.pub5